Adalimumab Biosimilars Demonstrate Long-Term Durability and Cost-Effectiveness in Paediatric Inflammatory Bowel Disease: A Real-World Two-Centre European Cohort Study - Ancona S; Armstrong K; Longo C; Rabone R; Merrick V; Henderson P; Gandullia P; Wilson DC; Arrigo S; Russell RK (Biologics: Targets & Therapy)
Silvana Ancona,1,2 Katherine Armstrong,2 Chiara Longo,3 Rosalind Rabone,2 Victoria Merrick,2 Paul Henderson,2,4 Paolo Gandullia,3 David C Wilson,2,4 Serena Arrigo,3 Richard K Russell2,4 1Department of Neuroscience, Rehabilitation, Ophthalmology, Genetics, Maternal and Child Health, University of Genoa, Genoa, Italy; 2Department of Paediatric Gastroenterology and Nutrition, Royal Hospital for Children and Young People, Edinburgh, UK; 3Paediatric Gastroenterology and Endoscopy Unit, IRCCS Istituto Giannina Gaslini, Genoa, Italy; 4Child Life and Health, University of Edinburgh, Edinburgh, UKCorrespondence: Richard K Russell, Royal Hospital for Children and Young People, 50 Little France Crescent, Edinburgh, EH16 4TJ, UK, Tel +44 131  312 0431, Email richard.russell@nhs.scotPurpose: Adalimumab biosimilars are increasingly used in paediatric Inflammatory Bowel Disease (PIBD), but data remain limited. This study assessed their durability, efficacy, safety and cost implications in PIBD.Patients and Methods: Consecutive PIBD patients who started adalimumab biosimilars between October 2018 and December 2023 at two centres in Scotland and Italy, with at least 6 months follow-up, were included. Demographic, disease, treatment, and adverse event data were collected. Disease activity was assessed at baseline, 6, 12, 24, 36 months, and at last follow-up. Durability was evaluated using Kaplan-Meier analysis.Results: In total 130 patients (81 males; median age 12.3 years) were included (115 Crohn’s Disease, 7 Ulcerative Colitis, 8 IBD unclassified). The biosimilars were ABP 501 (85%), GP2017 (14%), SB5 (1%); 41 (32%) patients switched from originator. After a median follow-up of 26 months, 87/130 (67%) patients remained on biosimilars, while 43 discontinued at a median of 14 months. Durability probabilities were 93%, 86%, 75%, 62%, and 57% at 6, 12, 24, 36, and 54 months, respectively. Patients previously exposed to ADA originator had a lower risk of biosimilar failure (hazard ratio, adjusted for age at diagnosis: 0.51 [95% confidence interval: 0.26– 0.99], p=0.047). Trough levels ≥ 11.6 μg/mL at 6 months were associated with greater durability (AUC=0.68, p=0.007). Adverse events occurred in 46/130 patients, mainly psoriasis and injection site reactions (13% each), with one lymphoma. Estimated cost savings were 5,030€ per patient/year.Conclusion: This real-life study demonstrated high durability and remission rates for adalimumab biosimilars in PIBD, confirming their clinical, cost-effectiveness and safety profile in children.Keywords: biosimilar, adalimumab, paediatric inflammatory bowel disease